Quatre priorités dans le financement international de la santé à considérer après le Sommet de Paris - Jacky Mathonnat (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– The recent Paris Summit "For a New Global Financial Pact" confirmed that international financing for development is a major concern for governments in the South and their external partners. Somewhat surprisingly, however, the issue of international financing for health remained off the agenda and sidelined from the debates. The aim of this note is therefore to contribute to reflection on international development financing from the specific perspectives of health. It examines four issues of particular importance to international financing in this sector. Firstly, it highlights the need for a massive increase in international health financing to reduce the gap that separates many developing countries from achieving Sustainable Development Goal 3 "Ensure good health for all, and promote well-being for all at all ages" by 2030. Health aid plays a crucial role in health financing in low-income countries, where its share is on average greater than that of governments. A sharp increase in net public health aid flows will be essential, as will a strong mobilization of private flows which have remained modest until now in low income countries. The challenges ahead are considerable. The note explains how this justifies making improving the efficiency of healthcare spending a top priority for governments and their external partners. Not to do so would be to squander resources that will remain woefully inadequate. Numerous studies show that there is significant room for manoeuvre, while in most low-income countries and in many middle-income countries, other approaches to widening fiscal space and easing the financial constraints on healthcare remain limited. Furthermore, Covid 19 highlighted the low resilience of many countries' healthcare systems when it comes to coping with pandemics. This is hardly surprising, given the low level of the main indicators to be considered. It is therefore imperative to strengthen countries' capacity to prepare and respond to the inevitable future pandemics, which in the immediate term means giving a major boost to the intervention capacity of the new, drastically under-resourced Pandemic Fund. Finally, the note makes the case for governments and their external partners to make more extensive use of SWAp in the health sector. Not all contexts lend themselves to SWAp, but when the environment is conducive to their use - particularly the quality of Public Financial Management (PFM) - they offer many potential advantages for improving the effectiveness and efficiency of health aid.
Keywords: 330; Health; Resilience; Efficiency; Health SWAps